Investment Feasibility Analysis of Rooftop Solar Power Plant for Spare Parts Supply Company - Wisudanto, Wisudanto; Qonitah, Iftinaniffah; Utomo, Wahyu (STMIK Widya Cipta Dharma, 2024)
A sustainable economic approach involves achieving economic growth while preserving the environment. One solution aligned with green economy initiatives is the Solar Power Plant (PLTS), which utilizes sunlight as the primary energy source to generate electricity. In response to increasing energy demand and growing environmental concerns, a spare parts supply company in Karawang, West Java, has decided to adopt hybrid energy by investing in renewable energy sources through the installation of an on-grid Solar Power Plant (PLTS) on the factory roof. This study aims to evaluate the financial feasibility of this green economic initiative. The analysis considers various aspects, including initial investment costs, operational and maintenance expenses for key components (solar modules and inverters), potential savings in electricity costs, and the projected return on investment over a specific period. The financial analysis methods applied include Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (DPP), and Profitability Index (PI) to determine the project's economic viability. The findings indicate that the DPP is 2.43 years (well below the 25-year lifespan), NPV is Rp 1,433,144,387.92 (positive and greater than 1), IRR is 46.31% (exceeding the 5.75% benchmark), and PI is 1.95 (greater than 1). Based on these results, it can be concluded that the construction of a rooftop solar power plant with an on-grid system is a financially viable investment for the spare parts supply company in Karawang, West Java.